Risk analysis in geotechnical works with the use of explosives - Cavalcante, Paulo Henrique; de Assis , André Pacheco (Seven Editora, 2023)
Analyzing Risk in Geotechnical Works is always a challenge for all specialists’ designers. Uncertainties of soil characteristics, better explosive, time and execution. All information should be well analyzed and criticized. Experience counts a lot, because the mature knowledge of standards is vital. Search, analyze and evaluate is a good way to study the possibilities of answers and so chose a topic - explosives and tested it. DOI:https://doi.org/10.56238/alookdevelopv1-182